2022
DOI: 10.1126/sciimmunol.abq7647
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T cells contribute to vaccine protection against SARS-CoV-2 in macaques

Abstract: Spike-specific neutralizing antibodies (NAbs) are generally considered key correlates of vaccine protection against SARS-CoV-2 infection. Recently, robust vaccine prevention of severe disease with SARS-CoV-2 variants that largely escape NAb responses has been reported, suggesting a role for other immune parameters for virologic control. However, direct data demonstrating a role of CD8 + T cells in vaccine protection has not yet been reported. In this study, we show that vaccine-elicited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 32 publications
6
87
1
Order By: Relevance
“…Multiple studies showed a key role for SARS‐CoV‐2‐specific CD8 + cytotoxic T cells in the modulation and resolution of COVID‐19 pathogenesis. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 Robust SARS‐CoV‐2‐specific CD8 + T cell immunity is associated with a mild disease outcome. 3 , 11 CD8 + T cells impair viral replication through recognition of viral peptide human leukocyte antigen class I (pHLA‐I) complexes displayed on the cell surface of infected cells, by which they accomplish rapid viral clearance and thereby reduce disease severity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies showed a key role for SARS‐CoV‐2‐specific CD8 + cytotoxic T cells in the modulation and resolution of COVID‐19 pathogenesis. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 Robust SARS‐CoV‐2‐specific CD8 + T cell immunity is associated with a mild disease outcome. 3 , 11 CD8 + T cells impair viral replication through recognition of viral peptide human leukocyte antigen class I (pHLA‐I) complexes displayed on the cell surface of infected cells, by which they accomplish rapid viral clearance and thereby reduce disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies showed a key role for SARS‐CoV‐2‐specific CD8 + cytotoxic T cells in the modulation and resolution of COVID‐19 pathogenesis 3–10 . Robust SARS‐CoV‐2‐specific CD8 + T cell immunity is associated with a mild disease outcome 3,11 .…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, COVIRS represents a significant resource for understanding the early innate and adaptive immune responses to mRNA and adenovirus vectored COVID-19 vaccines, and how these responses relate to immunogenicity and reactogenicity. The generation of high titers of Spike-specific binding and neutralizing antibodies is currently the best correlate of protection following vaccination against SARS-CoV-2, although the contribution of vaccine-induced T cells in protection from SARS-CoV-2 infection is becoming increasingly apparent (McMahan et al, 2021, Liu et al, 2022). Identifying the factors that promote the optimal generation of vaccine-specific T and B cell responses is a key priority and our study provides a wealth of data to inform future rational vaccine design.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have demonstrated that CD8+ T cells offer protection against SARS-CoV-2 [32,33] even in the absence of detectable antibody [34]. Likewise, in a study of people with haematological malignancy and COVID-19, those with higher CD8+ T cells had a greater survival despite a blunted humoral immune response [35].…”
Section: Plos Pathogensmentioning
confidence: 99%